2022
DOI: 10.3390/jof8111208
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabolomics Reveals Pathogenesis of Pestalotiopsis kenyana Causing Leaf Spot Disease of Zanthoxylum schinifolium

Abstract: Pepper leaf spot is a common disease of Zanthoxylum schinifolium. When it is serious, it directly affects the growth of Z. schinifolium, making the plant unable to blossom and bear fruit, which seriously restricts the development of the Z. schinifolium industry. Therefore, the pathogenic mechanism of leaf spots should be explored to provide a basis for a comprehensive understanding of the disease. Using liquid chromatography–mass spectrometry (LC–MS) technology combined with the data-dependent acquisition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Leaf spot on tea (Camellia sinensis (L.) O. Kuntze), caused by P. trachicarpicola, can negatively affect the production and quality of tea leaves [15]. Chang Liu et al [16] revealed the metabolites of P. kenyana were significantly different under the induction of Z. schinifolium leaves and metabolite 3, 5-dimethoxy benzoic acid, and S-(5-adenosyl)-L-homocysteine were identified as the most likely pathogenic substances. There is no report related to the P. kenyana infection in bayberry and their efficient control tragedy and mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf spot on tea (Camellia sinensis (L.) O. Kuntze), caused by P. trachicarpicola, can negatively affect the production and quality of tea leaves [15]. Chang Liu et al [16] revealed the metabolites of P. kenyana were significantly different under the induction of Z. schinifolium leaves and metabolite 3, 5-dimethoxy benzoic acid, and S-(5-adenosyl)-L-homocysteine were identified as the most likely pathogenic substances. There is no report related to the P. kenyana infection in bayberry and their efficient control tragedy and mechanism.…”
Section: Introductionmentioning
confidence: 99%